The Teaching English Vocabulary Through Crossword Puzzle at Eight Grade Students of SMP 1 Simanjaya In The Academic Year 2020/2021: Teaching English Vocabulary Through Crossword Puzzle at Eight Grade Students of SMP 1 Simanjaya In The Academic Year 2020/2021 - Afif Ardiansyah (JEET, Journal of English Education and Technology, 2021)
ABSTRACT This research aims to discuss Teaching English Vocabulary Through Crossword Puzzle for Eight Grade Students at SMP 1 Simanjaya Academic Year 2020/2021. This research uses quantitative with Pre-Experiment research. The data of this study are collected by Test and Observation. The technique of data analysis in this research uses analysis of the descriptive statistics technique for analyzing the test data, and percentage for analyzing the observation data. The result of that Crossword Puzzle Media is effective to increase vocabulary ability at the students of eight grade students SMP 1 Simanjaya. It can be seen from the paired samples test showed sig (2-tailed) score 0,000 < 0,05 which mean that there was significant effect of Crossword Puzzle Media to increase students’ vocabulary mastery.